Widening Opportunities for Increased Marketing of Processed Milk in Uganda Introduction - Mbowa, Swaibu; Shinyekwa, Isaac; Mayanja Lwanga, Musa (Economic Policy Research Centre (EPRC), 2012)
The analysis of the 2009 Uganda National panel Survey (UNPS) collected by the UBoS shows that milk production from smallholder farm units was 1 billion litres, and about 52 percent (524 million litres) joined the second level of the milk value chain – and of which 72 percent was marketed in unprocessed form to consumers. High informality in milk marketing can be reduced by supporting strong primary dairy farmers’ cooperative societies with capacity to invest in processing of scale neutral dairy products (yoghurts, ghee and cheese), at the same time hold strong bargaining power with large milk processing companies. This would allow the deeper participation of farmers (as groups) in the down-stream milk value chain, and enable having the right price incentives to draw more raw milk into the formal stream of the milk value chain. This would foster equitable spread of benefits and opportunities from the growing domestic demand for milk and other dairy products at all levels of the milk value chain.